2000
DOI: 10.1073/pnas.97.15.8664
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric acid type B receptors are expressed and functional in mammalian cardiomyocytes

Abstract: ␥-Hydroxybutyrate (GHB), an anesthetic adjuvant analog of ␥-aminobutyrate (GABA), depresses cell excitability in hippocampal neurons by inducing hyperpolarization through the activation of a prominent inwardly rectifying K ؉ (Kir3) conductance. These GABA type B (GABAB)-like effects are clearly shown at high concentrations of GHB corresponding to blood levels usually reached during anesthesia and are mimicked by the GABAB agonist baclofen. Recent studies of native GABAB receptors (GABABRs) have favored the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…As in neurons, both GHB (see sect. IIIB2) and baclofen activate an inwardly rectifying K ϩ channel in rat cardiomyocytes (199). GABA B(1) and GABA B(2) expression in cardiomyocytes was confirmed by immunoblotting and in coimmunoprecipitation studies.…”
Section: Cellular and Subcellular Distributionmentioning
confidence: 84%
“…As in neurons, both GHB (see sect. IIIB2) and baclofen activate an inwardly rectifying K ϩ channel in rat cardiomyocytes (199). GABA B(1) and GABA B(2) expression in cardiomyocytes was confirmed by immunoblotting and in coimmunoprecipitation studies.…”
Section: Cellular and Subcellular Distributionmentioning
confidence: 84%
“…Several studies indicate the possible expression of functional GABA B receptors in peripheral and nonneuronal cells such as pancreatic b cells (16), adrenocortical cells (17), cardiomyocytes (18), chondrocytes (19), and osteoblasts (20). Furthermore, GABA B R1 mRNA expression was detectable using RT-PCR analysis in many peripheral organs, including heart, spleen, lung, liver, intestine, kidney, stomach, adrenal gland, testis, ovary, and urinary bladder (21).…”
Section: Discussionmentioning
confidence: 99%
“…The staining pattern on the surface of the sperm head with anti-GABABR2 antibody resembled the distribution reported previously with anti-GABABR1 antibody [18], indicating possible congruent localization of both receptors on the head of rat sperm. Lorente et al [23] reported that functional GABABR is composed of both GABABR1 and GABABR2 and is present in rat cardiomyocytes. This finding combined with our present results indicates hat the GABA B R2 subunit occurs in rat testis, sperm and other tissues and is not restricted to the CNS.…”
Section: Resultsmentioning
confidence: 99%